2018
DOI: 10.1080/0020739x.2018.1440325
|View full text |Cite
|
Sign up to set email alerts
|

Investigating secondary students beliefs about mathematical problem-solving

Abstract: Many studies over the past thirty years have highlighted the important role of students' beliefs for successful problem solving in mathematics. Given the recent emphasis afforded to problem solving on the reformed Irish secondary school mathematics curriculum, the main aim of this study was to identify Irish students' (n = 975) beliefs about the field. A quantitative measure of these beliefs was attained through the use of the Indiana Mathematical Belief Scale, an existing thirty item (five scale) self-report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
11
0
5
Order By: Relevance
“…As such, while the reform encourages the collaborative and realistic approaches described in feminist mathematics pedagogy (Anderson 2005;Spielman 2008), it is evident that girls are still struggling with lower confidence in having to implement a scientific problem-solving approach. This is further supported by Prendergast et al (2018), who found that, in Ireland, female students had lower belief in their ability to solve time-consuming problems than their male peers and had lower levels of belief that effort could increase mathematical ability. This could be considered one of the factors in the continually negative attitudes of females to mathematics, despite the increase of more modern, inclusive methodologies.…”
Section: Do Gender Differences Exist Regarding Confidence and Mathematical Self-concept?mentioning
confidence: 63%
“…As such, while the reform encourages the collaborative and realistic approaches described in feminist mathematics pedagogy (Anderson 2005;Spielman 2008), it is evident that girls are still struggling with lower confidence in having to implement a scientific problem-solving approach. This is further supported by Prendergast et al (2018), who found that, in Ireland, female students had lower belief in their ability to solve time-consuming problems than their male peers and had lower levels of belief that effort could increase mathematical ability. This could be considered one of the factors in the continually negative attitudes of females to mathematics, despite the increase of more modern, inclusive methodologies.…”
Section: Do Gender Differences Exist Regarding Confidence and Mathematical Self-concept?mentioning
confidence: 63%
“…Al contextualizar los problemas, Prendergast et al, (2018) sugiere que las creencias de los estudiantes sobre la utilidad del curso tienen relación con su desempeño en la resolución de problemas por lo que deja en claro que existe un vínculo entre las creencias de los estudiantes sobre la resolución de problemas en matemáticas y su desempeño en la materia. La gran mayoría de estudiantes manifiesta ciertas creencias según como haya sido su experiencia en años anteriores, según como lo han experimentado sus padres o incluso sus mismos docentes.…”
Section: Discusión De Resultadosunclassified
“…Desde muchos años, existe una creciente preocupación ya generalizada porque la resolución de problemas sea una actividad del pensamiento como resultado del análisis-razonamiento y no una mera aplicación repetitiva y mecánica de algoritmos con la única intención de obtener un resultado sin el debido tiempo de razonar si dichos procedimientos responden a la solución del problema (Prendergast et al, 2018;Lane et al, 2016;Gijsbers et al, 2019). En la mayoría de los casos se ve que se trata de una mera aplicación de algoritmos repetidos sin operacionalizar las situaciones problemáticas de la vida real donde se pueda medir las competencias interpretativas y argumentativas de las mismas.…”
Section: Introductionunclassified
“…Students believe that attempts to study can motivate them to successfully solve mathematics problems (Prendergast et al, 2018).…”
Section: Effortmentioning
confidence: 99%